Objectivity and subjectivity criteria in english examination testing during the pandemic - Blinov, Mikhail (Pedagogy and Psychology, 2021)
Exams, being a good way to measure the academic achievement, can cause students serious psychological problems. One of the ways to eliminate stressful situations is to maximize the objectivity of students’ assessment during examination testing. The article analyses the measures to reduce the subjectivity of assessment during examination testing in the context of a pandemic. Options for conducting examination testing at the university, at home and with the participation of a proctor are offered. Pros and cons of proctoring are discussed. The procedure for examination testing and the conditions for its implementation in the context of a pandemic are described in detail. The article provides a practical example of conducting an examination test in the specialty "Jurisprudence". The article considers the alternatives to examination testing. The author concludes saying that it is necessary to combine traditional and distance learning methods after the end of the pandemic period in Kazakhstan.